Long-term outcomes of percutaneous left atrial appendage closure for the prevention of stroke in patients with atrial fibrillation: Asia-Pacific experience - Fu-Chun Chiu; Pang-Shuo Huang; Jien-Jiun Chen; Juey-Jen Hwang; Chia-Ti Tsai (Journal of the Formosan Medical Association, 2022)
Background/Purpose: In patients with non-valvular atrial fibrillation (NVAF), the left atrial appendage occluder (LAAO) is an alternative treatment for stroke prevention. However, the long-term outcomes in Asia was generally unknown. Methods and Results: This was a retrospective longitudinal study and a total of 124 patients with contraindications to oral anticoagulants or stroke despite under anticoagulants had been enrolled since 2013. Primary efficacy was defined as any type of stroke/systemic embolization and adverse event as any procedure or anti-thrombotic related complications. Twelve patients were excluded due to thrombus in the LAA or oversize LAA. Watchman was successfully implanted in 55 patients (98%) and ACP/Amulet also 55 patients (98%). During follow-up, the ischemic stroke rate was 1.9 in the Watchman and 1.4 per 100 patient-year in the ACP/Amulet group. There were 2 Watchman patients experiencing intracranial hemorrhage. Device-related thrombus (DRT) was noted in 3 patients (2.7%).There was no patient with peri-device lead ≧5 mm. In those patients receiving only local anesthesia, the follow-up echocardiography showed no significant peri-device leak, malposition of LAAO and DRT. Conclusion: This long-term follow-up study shows that percutaneous closure of LAA is a safe and technically feasible procedure with satisfactory outcomes in Asia. The procedure success rate, efficacy and adverse event were similar to those reported in the Caucasian populations.